Pete the Kitty and the mermaid's sandcastle [book with audioplayer] - Dean, Kim, 1969-; Dean, James, 1957- (Pete the kitty., 2025)
"Pete the Kitty and his mermaid friend Jessie work together to build a sandcastle. But the castle is missing something. Will one shell, two barnacles, three strands of seaweed, and more gifts from the sea be enough to make their sandcastle the best it can be?"--